HUBUNGAN KECEPATAN LARI 40 METER DAN DAYA LEDAK OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS XI IPS1 MAN 1 MUARA FAJAR PEKANBARU - Anwar, Khairul; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the low of student’s ability to reach their target which is a leap of 4.30 meters. The purpose of the research is to determine whether there is a relationship of the speed 40 meters run and the explosive of power leg muscles to squat-style long jump results in male student of XI Social1 MAN 1 Muara Fajar Pekanbaru. The sampling is the overall population (total sampling) of Male Student of XI Social1 MAN 1 Muara Fajar Pekanbaru which consists of 17 students. The test forms Correlation Techniques. The test data uses normality tests, Product Test Moment Correlation, significant test α = 0:05. The Normality test variables X1, L 0 max (0.1885) <L table (0.206), X2, L 0 max (0.1349) <L table (0.206) and normality test variables Y, L 0 max (0.1369 )<L table (0.206), in other words the level of normal data and the conclusions of research illustrates that there is a significant correlation between the relationship running speed and the explosive of power leg muscle with the results of the long jump, with a correlation of r = 0.497 where r count> r table or 0.497 > 0.510. The categorized of the relationship is strong. Thus, Ho is rejected and Ha is accepted.Key Words: 40 Meter Run Speed, Limb Muscle and Power Explosive Long Jump Results